Municipalities Central to Decade of Future Investments - Katja Rietzler (Wirtschaftsdienst)
Abstract In the coalition agreement, the new federal government holds out the prospect of a “decade of investment for the future”. It thus recognises that considerable additional investment-related government spending is necessary to overcome the investment backlog in Germany and promote the socio-ecological transformation. Based on current studies, a total of 600 to 800 billion euros over ten year seems plausible, with a significant share accruing at the municipal level. The new government addresses important problems of municipal finances including significant regional disparities, but further measures are needed to enable all local communities to invest sufficiently.